2016
DOI: 10.1080/10408398.2014.906382
|View full text |Cite
|
Sign up to set email alerts
|

Health-promoting effects of the citrus flavanone hesperidin

Abstract: Hesperidin, a member of the flavanone group of flavonoids, can be isolated in large amounts from the rinds of some citrus species. Considering the wide range of pharmacological activities and widespread application of hesperidin, this paper reviews preclinical and clinical trials of hesperidin and its related compounds, including their occurrence, pharmacokinetics, and some marketed products available. Preclinical studies and clinical trials demonstrated therapeutical effects of hesperidin and its aglycone hes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
166
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(180 citation statements)
references
References 140 publications
2
166
0
1
Order By: Relevance
“…In this study, as shown in Figures 5 and 8, compared with model group, Nrf2 and its target genes (HO-1, NQO1, GST, and r-GCS) were up-regulated by TFCH treatments in vivo and in vitro, demonstrating the therapeutic mechanism of TFCH against NASH was related with Nrf-ARE signaling. Flavonoids product has numerous biological properties, which may be promising therapeutic agents for NASH (Li and Schluesener, 2017). Many natural products are rich in flavonoids and possess anti-oxidative and anti-inflammatory activities against NASH (Jian et al, 2018;Parafati et al, 2018;Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, as shown in Figures 5 and 8, compared with model group, Nrf2 and its target genes (HO-1, NQO1, GST, and r-GCS) were up-regulated by TFCH treatments in vivo and in vitro, demonstrating the therapeutic mechanism of TFCH against NASH was related with Nrf-ARE signaling. Flavonoids product has numerous biological properties, which may be promising therapeutic agents for NASH (Li and Schluesener, 2017). Many natural products are rich in flavonoids and possess anti-oxidative and anti-inflammatory activities against NASH (Jian et al, 2018;Parafati et al, 2018;Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemicals, such as flavonoids of herbs and fruits showed chemopreventive effects against multiple human cancers . Hesperidin is a flavanone glycoside that is found in the Citrus species . It has been reported with antioxidant, anti‐inflammatory, and antifibrotic activities.…”
Section: Introductionmentioning
confidence: 99%
“…The role of oxidative stress in UC has been documented as chronic intestinal inflammation is associated with reactive oxygen and nitrogen species leading to oxidative and nitrosative stress . Hesperetin‐7 rutinoside (HES) is one of the flavonoids that constitutes citrus fruits and is found naturally as glycosides . The microflora of the distal part of the small intestine and colon hydrolyses hesperidin into aglycones and hesperetin .…”
Section: Introductionmentioning
confidence: 99%